Analisis Penerapan Kompetensi Pedagogik Guru Sekolah Dasar Dalam Melaksanakan Pembelajaran Matematika Kelas VI SD - Sianturi, Helen; Lusa, Herman; Yusnia (JURIDIKDAS, 2024)
This study aims to describe the application of pedaogogic competence of elementary school teachers in implementing in mathematics learning in class VI SD Negeri 17 Bengkulu City. This research uses qualitative research methods using a qualitative descriptive approach. Data collection techniques through observation, interviews, and documentation. Data analysis techniques are carried out by collecting data in the field, reducing data, presenting data, and drawing conclusions. Data validity in conducting credibility tests used are triangulation and member check. The results showed that the pedagogical competence of class VI A teachers in the implementation of mathematics learning based on seven indicators has been implemented, teachers can understand the characteristics of students, are able to master learning theories and principles of educational learning, carry out curriculum development, carry out educational learning activities, develop the potential of students and carry out evaluation and assessment. However, of the seven indicators of pedagogical competence, there is one indicator that has not been fully met, namely the fourth indicator of educational learning activities. Teachers do not utilize technology in learning such as infocus and learning videos in the learning process.